Biocultural Drivers of Salivary Microbiota in Australian Aboriginal and Torres Strait Islander Children - Handsley-Davis, Matilda; Skelly, Emily; Johnson, Newell W.; Kapellas, Kostas; Lalloo, Ratilal; Kroon, Jeroen; Weyrich, Laura S. (Frontiers in Oral Health, 2021)
Australian Aboriginal and Torres Strait Islander children experience unacceptably high rates of dental caries compared to their non-Indigenous Australian counterparts. Dental caries significantly impacts the quality of life of children and their families, particularly in remote communities. While many socioeconomic and lifestyle factors impact caries risk, the central role of the oral microbiota in mediating dental caries has not been extensively investigated in these communities. Here, we examine factors that shape diversity and composition of the salivary microbiota in Aboriginal and Torres Strait Islander children and adolescents living in the remote Northern Peninsula Area (NPA) of Far North Queensland. We employed 16S ribosomal RNA amplicon sequencing to profile bacteria present in saliva collected from 205 individuals aged 4–17 years from the NPA. Higher average microbial diversity was generally linked to increased age and salivary pH, less frequent toothbrushing, and proxies for lower socioeconomic status (SES). Differences in microbial composition were significantly related to age, salivary pH, SES proxies, and active dental caries. Notably, a feature classified as Streptococcus sobrinus increased in abundance in children who reported less frequent tooth brushing. A specific Veillonella feature was associated with caries presence, while features classified as Actinobacillus/Haemophilus and Leptotrichia were associated with absence of caries; a Lactobacillus gasseri feature increased in abundance in severe caries. Finally, we statistically assessed the interplay between dental caries and caries risk factors in shaping the oral microbiota. These data provide a detailed understanding of biological, behavioral, and socioeconomic factors that shape the oral microbiota and may underpin caries development in this group. This information can be used in the future to improve tailored caries prevention and management options for Australian Aboriginal and Torres Strait Islander children and communities.